DIAGNOSTIC OF WATER VAPOR ADSORPTION MOLAR HEAT AND ACCUMULATION AT BUBBLE SURFACE DURING AERATION TREATMENT IN SATURATION PERIOD - Ševaljević, Mirjana; Simić, Stojan; Stanojević, Miroslav; Pavlović, Milan; Ševaljević, Miladin (Journal of Applied Engineering Science, 2015)
Diagnostics of adsorbed water vapor molar heat and accumulation at bubble surface during refinery waste water aeration treatment with membrane distributor was performed, on the basis of experimentally measured air temperature and pressure on input and exit and measured stationary oxygen content after saturation period. The working hypothesis is that electromotor and compressor favor the consumption of water vapor adsorption heat at bubbles surfaces and the relaxation with active centers transport work, according to II law of thermodynamic. During air over-pressure relaxation, active centers enable the couple of prevented exothermic hydration and favored endothermic processes and water vapor accumulation up to catalyst final titration points in zone of condensation, precipitatation, vaporization, nitrification/denitrification and biological slime that can cause diffuser fouling and scalling. Diagnostics results for the all 15 examined systems with the same membrane diffuser and various combination of process parameters, c-h-q: without and with added motor oil, c = 0 mg/l   5 mg/l   and 10 mg/l, with two heights of water column, h =1m and 2 m and with three air flows, q=2m3/h, 6m3/h and 10 m3/h verified the linear functional dependence of indicator of proper process condition, i.e.  experimental determined oxygen saturation degree on water vapor accumulation (R2=0.766).
Keywords: accumulation; Adsorption; Air; Bubbles; Heating; molarity; oxygen; saturation; vaporization; water vapor